Formation of multiphase plasma in galactic haloes and an analogy to solar plasma - Choudhury, Prakriti Pal (Frontiers in Astronomy and Space Sciences, 2023)
Thermal instability (TI) potentially explains the origin of cold gas in the intracluster medium (ICM), which is heated sufficiently by AGN feedback. The H$α$ filaments seen in cluster cores provide strong motivation for TI. The hot ($\sim 10^7$ K) ICM coronae allows the growth of isobaric TI. Multiphase medium (cold-dense — hot-diffuse) forms once TI saturates. However, gravitational stratification can spatially constrain TI, and {\color{red} thermal conduction is known to stabilize all scales below the Field length ($λ_{\rm F}$). In addition, the transport of energy is anisotropic along magnetic fields. Thermal conduction may further trigger gyro-scale instabilities and effective reduction of $λ_{\rm F}$. But cold gas at small scales ($< λ_{\rm F}$) needs to be verified in observations. The virial temperature in galactic haloes is lower ($\sim 10^6$ K) and opens the regime of isochoric TI}. In this regime, cooling time is typically shorter than sound-crossing time, and large-scale isochoric clouds are rendered unstable. The linear and non-linear isochoric clouds have interesting differences which potentially lead to either fragmentation of the cloud or not. On saturation, TI produces a turbulent medium that helps to mix phases, thermalize kinetic energy, and thus completes a cycle of condensation and heating. Various aspects of condensation, stratified turbulence, and magnetized transport are physically identical in solar coronae but scaled down to {\color{red} lower luminosity (similar temperatures)}. We will discuss the recent progress in TI, its connection to observations, and the analogy to solar prominences.